THE EFFECT OF WORK DISCIPLINE, WORK ENVIRONMENT AND WORK MOTIVATION ON EMPLOYEES’ PERFORMANCE AT THE PORT AUTHORITY AND HARBORMASTER OFFICE CLASS II TELUK PALU - Febrilita, Febrilita; Thahir, Harifuddin; Evvy Rossanty, Niluh Putu (Master of Management Study Program, Faculty of Economics and Business, Tadulako University, 2021)
This study aims to analyze the effect of work discipline, work environment, and work motivation on employees’ performance at the Port Authority and Harbormaster Office Class II Teluk Palu. This study applied a survey type and causal descriptive using a research population of 80 civil servants at the Port Authority and Harbormaster Office Class II Teluk Palu where all employees are designated as research samples through the census method. The data analysis technique used multiple linear regression analysis. The result of this study indicates that work discipline, work environment, and work motivation variables simultaneously have a significant effect on employees’ performance at the Port Authority and Harbormaster Office Class II Teluk Palu, with a Sig-F value of 0.000 < α 0.05. The work discipline variable partially has a significant effect on employees’ performance at The Port Authority and Harbormaster Office Class II Teluk Palu with a Sig-t X1 value is 0.000 < α 0.05; The work environment variable partially has a significant effect on employees’ performance at The Port Authority and Harbormaster Office Class II PTeluk Palu with a Sig-t X2 value of 0.018 < α 0.05; and the work motivation variable partially has a significant effect on employees’ performance at the Port Authority and Harbormaster Office Class II Teluk Palu with a Sig-t X3 value is 0.029 < 0 α.05. Keywords: Work Discipline, Work Environment, Work Motivation, Employees’ Performance